Loose binding of the DF axis with the A3B3 complex stimulates the initial activity of Enterococcus hirae V1-ATPase. - Md Jahangir Alam; Satoshi Arai; Shinya Saijo; Kano Suzuki; Kenji Mizutani; Yoshiko Ishizuka-Katsura; Noboru Ohsawa; Takaho Terada; Mikako Shirouzu; Shigeyuki Yokoyama; So Iwata; Yoshimi Kakinuma; et al. (PLoS ONE)
Vacuolar ATPases (V-ATPases) function as proton pumps in various cellular membrane systems. The hydrophilic V1 portion of the V-ATPase is a rotary motor, in which a central-axis DF complex rotates inside a hexagonally arranged catalytic A3B3 complex by using ATP hydrolysis energy. We have previously reported crystal structures of Enterococcushirae V-ATPase A3B3 and A3B3DF (V1) complexes; the result suggested that the DF axis induces structural changes in the A3B3 complex through extensive protein-protein interactions. In this study, we mutated 10 residues at the interface between A3B3 and DF complexes and examined the ATPase activities of the mutated V1 complexes as well as the binding affinities between the mutated A3B3 and DF complexes. Surprisingly, several V1 mutants showed higher initial ATPase activities than wild-type V1-ATPase, whereas these mutated A3B3 and DF complexes showed decreased binding affinities for each other. However, the high ATP hydrolysis activities of the mutants decreased faster over time than the activity of the wild-type V1 complex, suggesting that the mutants were unstable in the reaction because the mutant A3B3 and DF complexes bound each other more weakly. These findings suggest that strong interaction between the DF complex and A3B3 complex lowers ATPase activity, but also that the tight binding is responsible for the stable ATPase activity of the complex.